ANALYTICAL STUDY OF THE EGYPTIAN MILITARY FORTIFICATIONS UNTIL THE END OF THE MIDDLE KINGDOM - Nancy Hosam Mahmoud (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2021)
The study of Egyptian castles and fortresses is one of the important topics in the field of Egyptian antiquities in general and Egyptian architecture in particular. It is also unique in studying military architecture because Egypt witnessed many conflicts and wars, of which these castles and forts were the most important results. Castles and forts refer to the interest of the kings of this era in building castles and fortresses, to repel foreign invasions. This research deals with an analytical study of the Egyptian military fortifications until the end of the middle kingdom, through several axes, including: The analytical study of the forts of the pre-dynastic era, the era of the Old Kingdom and the era of the Middle Kingdom, and through each of these axes, models of the forts were dealt with in each of the historical periods covered by the research, which extends from the pre-dynastic era until the end of the Middle Kingdom. The study also dealt with the advantages of the architectural planning of the forts in these ages.